The reckoning - Yrsa Sigurðardóttir (Minotaur Books, 2019)
Vaka sits, regretting her choice of coat, on the cold steps of her new school. Her father appears to have forgotten to pick her up, her mother has forgotten to give her this week<U+2019>s pocket money, and the school is already locked for the day. Grownups, she decides, are useless. With no way to call home, she resigns herself to waiting on the steps until her father remembers her. When a girl approaches, Vaka recognizes her immediately from class, and from her unusual appearance: two of her fingers are missing. The girl lives at the back of the school, on the other side of a high fence, and Vaka asks to call her father from the girl's house. That afternoon is the last time anyone sees Vaka. Detective Huldar and child psychologist Freyja are called in. Soon, they find themselves at the heart of another shocking case.